Criminalization of Sexual Workers: a Study of International Covenants on Women’s Trafficking - Lorensia Brahmana (Jurnal Perempuan, 2015)
This article looks into the actions taken by the Government of Indonesia to follow up the integration of the points of the Beijing Platform +20 into national instruments such as legislation products, law, and public policy based on gender equality in accordance with suppressing women trafficking particularly the exploitation of prostitution pinpointed by the Beijing Platform +20. It will also discuss gender injustice as the root of women’s trafficking. Women exploitation in prostitution still can not be addressed optimally by the government because of gender inequality in legal structure and system. Besides, the implementation is still based on genderbiased value and construction of sexuality in patriarchal society.